Aplikasi Presensi Berbasis Web Pada UPT SD Negeri 1 Sidodadi Sebagai Manajeman Administrasi Kehadiran Siswa - Suyono, Suyono; Hamid, Abdul (YHMM PUBLISHING, 2025)
Basically, technology is needed in various fields, especially in education. In education, technology must be utilized as much as possible, especially in managing attendance for students, teachers and education personnel. At UPT SD Negeri 1 Sidodadi, attendance management is still done manually. With the manual method, sometimes the attendance data is inaccurate, there are too many files in the form of paper that pile up, making it difficult to summarize and difficult to find the data needed on a particular day or month. Therefore, this study aims to design a web-based attendance management application at UPT SD Negeri 1 Sidodadi which is still done manually. With the data input application, it will be more efficient and accurate, because schools are required to work quickly. For this reason, research was conducted using observation and interview methods to obtain accurate and reliable information data which then entered the application system design stage. The design of this web-based attendance application uses PHP (Hypertext Preprocessor) and MySQL Database which makes it easy to store large amounts of data. With the design of this application, it is expected to facilitate the management of the presence of Students, Teachers and Education Personnel at UPT SD Negeri 1 Sidodadi. The management of attendance that already uses a system and is structured will later facilitate reporting of attendance both daily, monthly and semesterly. Not only for UPT SD Negeri 1 Sidodadi but can be applied to other educational institutions that still use manual methods.